Cosmopolitanism and migrations: American projection of Freemasonry from the county of Campo de Gibraltar - Morales Benítez, Antonio (2020)
El Campo de Gibraltar county had close masonic links with America. This cosmopolitanism took place in both directions. One of the promoters of the Masonic expansion in Spain became acquainted with the Order in Havana. Also, the founder and venerable master of the first lodge of the 20th century in El Campo later started a lodge in the American city of Tampa. Subsequently, other freemasons would migrate to cities such as New York. Also, after the Spanish civil war the American continent became a place of exile for some of them.